ANALISIS PERBEDAAN RETURN SAHAM DAN VOLUME PERDAGANGAN SAHAM SEBELUM DAN SESUDAH PENGUMUMAN DIVIDEN TAHUN 2017 (Studi Empiris Pada Perusahaan yang Terdaftar di Bursa Efek Indonesia) - Puji Sulastri (JURNAL EKOBIS DEWANTARA, 2018)
The purpose of this study is to determine whether there is (1) the effect of dividend announcement on stock return before, during and after and (2) trading volume of stock before, during and after on company listed in Indonesia Stock Exchange (BEI) in 2017. In this research classified type of quantitative research. The population is all companies listed in Indonesia Stock Exchange (BEI) in 2017. The sample of research is 3 companies in different sectors, namely: (1) Astra Agro Lestari Tbk (AALI), (2) United Tractors Tbk (UNTR), (3) ) PT Acset Indonusa Tbk (ACST). Data collection method using documentation method, while technique of data analysis using different test that is T test (T-test). The result of the research shows that stock return test in the period before with after dividend announcement is known that sig. 0.721 which means not proven, stock return in the period before with the time of dividend announcement known that sig. 0,000 which means proven and stock returns in the current period with after dividend announcement known sig. 0,000 which means proven. From the test results of trading volume of shares in the period before with after the announcement of dividend known that sig. 0,000 which means proven. In the period before the time of dividend announcement is known that sig. 0,000 which means proven and in the period when after the dividend announcement is known that sig. 0,000 means proven.